The Relationship between Sleep Characteristics and Emotions and Behavior in School-age Children: a Study on the Mediating Effect of Executive Function - MA Ning, ZHAO Yang, LYU Shaobo, ZHANG Haodong, WANG Changming, MENG Jie (Zhongguo quanke yixue, 2024)
Background The sleep characteristics of school-age children have a crucial impact on the development of emotional and behavioral problems. Sleep characteristics also play a role in the development of executive function in school-age children. There is a close relationship between the emergence of emotional and behavioral problems and the development of executive function in these children. Currently, there are few studies on the mediating effect of the relationship between sleep characteristics, executive function, and emotional and behavioral problems in school-age children. Objective To explore the relationship between sleep characteristics, executive function, and emotional and behavioral problems in school-age children, and to examine the mediating role of executive function in the relationship between sleep characteristics and emotional and behavioral problems. Methods From August 21 to October 8, 2021, a convenience sampling method was used to select 516 school-age children from grades 1 to 6 in Xiwu Primary School and the Fourth Experimental Primary School in Shexian County, Handan City, Hebei Province. The Children's Sleep Habits Questionnaire (CSHQ), the Strengths and Difficulties Questionnaire (SDQ), and the Behavior Rating Inventory of Executive Function (BRIEF) were used to assess the sleep characteristics, emotional and behavioral problems, and executive function of the school-age children, respectively. Correlation analysis, regression analysis, and mediation analysis were conducted using SPSS 27.0 and the PROCESS 4.1 plugin. Results A total of 516 questionnaires were distributed, and 496 valid questionnaires were recovered, with an effective recovery rate of 96.1%. Correlation analysis showed that the total score of the CSHQ was negatively correlated with the Behavioral Regulation Index (BRI), Metacognition Index (MI), inhibition, shifting, emotional control, task initiation, working memory, planning, organization, and monitoring factors of the BRIEF (P<0.001). The total score of the SDQ was positively correlated with the BRI, MI, inhibition, shifting, emotional control, task initiation, working memory, planning, organization, and monitoring factors of the BRIEF (P<0.001). Forced entry method results showed that sleep characteristics negatively predicted emotional and behavioral problems (B=-0.15, t=-5.33, P<0.01), while executive function positively predicted emotional and behavioral problems (B=0.13, t=20.88, P<0.01). Mediation analysis showed that when executive function, BRI, and MI were used as mediating variables, there was a complete mediating effect between sleep characteristics and emotional and behavioral problems in children. The 95%CI for both the main effect and the indirect effect did not include 0 (P<0.001), and the 95%CI for the direct effect included 0 (P>0.05) . Conclusion There is a close relationship between sleep characteristics, executive function, and emotional and behavioral problems in school-age children. Executive function has a complete mediating effect on the relationship between sleep characteristics and emotional and behavioral problems. This finding emphasizes the importance of good sleep for the behavioral and emotional well-being of school-age children and provides new perspectives and intervention approaches for enhancing executive function and overall development in school-age children.